The Effect of Planting Media and Compound Fertilizers on The Growth of Rubus pyrifolius J. E. Smith Seedling - Surya, Muhammad Imam; Rahman, Wiguna (AGRIVITA, Journal of Agricultural Science, 2011)
The experiment was conducted from June to October 2009, at Cibodas Botanical Garden. The design used in the experiment was completely randomized block with two treatments and three replicates. The first factor was four kinds of planting media (sand + husk (2:1), sand + compost (1:1), husk + compost (1:1), compost). The second factor was three kinds of fertilizers (growmore, gandasil D, hyponex) and one treatment without fertilizer (control). The results of experiment show no interaction in almost all parameters between planting media and compound fertilizers. Statistically, all parameters observed show significance (? = 0,05 and ? = 0,01) at various media. Based on the study, the best media were compost and sand + compost (1:1). These media were recommended for R. pyrifolius seedling growth.Keywords : Rubus pyrifolius, planting media, fertilizers